A Model Describing the Rhetorical Structure of the Abstracts of Cardiology Research Articles in English - Angel Rodríguez, Naliet; Bernal Díaz, Pedro Santiago; Rodríguez Ruiz, Mayra (My University, 2021)
The Abstract section of the research article (RA) is particularly important because it offers different communicative functions. In the medical field, English has also gained the status of Lingua Franca since most of the medical journals are published in English and principal contributions in medicine and science are published in this language as well. Therefore, it is essential for scientists in the field of medicine to communicate the results of their research in English in order to gain international recognition.
Keywords: Genre analysis; Research article abstract; Discourse community